2023
DOI: 10.3390/diseases11010032
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy in Sub-Saharan Africa in the Context of COVID-19 Vaccination Exercise: A Systematic Review

Abstract: Presently, the COVID-19 vaccine is seen as a means to an end in light of other challenges, such as vaccine inequity. Through COVID-19 Vaccines Global Access (COVAX), an initiative founded to guarantee fair and equitable distribution, vaccine hesitancy remains a critical component that needs to be addressed in sub-Saharan Africa. Utilizing a documentary search strategy and using the keywords and subject headings Utilitarianism and COVID-19 or Vaccine hesitancy and sub-Saharan Africa, this paper identified 67 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…31,32 COVID-19 vaccine hesitancy occurs against a backdrop of social-cultural complexities, poor government response in demystifying social and traditional myths and theories, and poor community involvement in public health measures. 33 Pregnant women in our study reported not having adequate information about the COVID-19 vaccine and were therefore concerned about the side effects of the vaccine on their pregnancy, vaccine safety, and efficacy, findings which were similar to an earlier study by Dinga et al 34 In our study, religious affiliation was not associated with vaccine hesitancy, and neither was the need to seek permission for vaccination from a family member or partner.…”
Section: Vaccine Uptake Over Timesupporting
confidence: 84%
“…31,32 COVID-19 vaccine hesitancy occurs against a backdrop of social-cultural complexities, poor government response in demystifying social and traditional myths and theories, and poor community involvement in public health measures. 33 Pregnant women in our study reported not having adequate information about the COVID-19 vaccine and were therefore concerned about the side effects of the vaccine on their pregnancy, vaccine safety, and efficacy, findings which were similar to an earlier study by Dinga et al 34 In our study, religious affiliation was not associated with vaccine hesitancy, and neither was the need to seek permission for vaccination from a family member or partner.…”
Section: Vaccine Uptake Over Timesupporting
confidence: 84%
“…These associations provide evidence that the campaign contributed significantly to beneficial changes in attitudes and practices and that it had an additive effect, layering on top of increased public concern about the second wave and the perceived threat level. The importance of adopting non-coercive public policies and actions to encourage vaccine acceptance, as well as factors such as public trust and community involvement has been emphasised [ 31 ]. Given the ongoing conflict and fragile nature of the political situation in Somalia, the apparent success of the campaign is remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional media and healthcare workers were identi ed in this study as the common sources of vaccine information¸ and the level of vaccination hesitancy was linked to the information source for different demographics like pregnant and lactating mothers. In a systematic review to determine the factors driving vaccine hesitancy in SSA, public distrust was also common as a hindrance to the administration of Covid-19 vaccination, with the governments' poor handling of the pandemic leading to a lack of trust from the general public, alongside the backdrop of colonialism that drives the refusal of vaccines shipped from abroad [31]. This was similar to research done in Ghana targeting 2345 adults and conducted from 23 to 28 February 2021 and whose ndings showed those hesitating to get vaccinated were not well informed about the possible side effects (60%), were unsure about the clinical safety of te jab (41%), not sure of the vaccine effectiveness in preventing Covid-19 infection (23%) [32].…”
Section: Vaccine Acceptance/hesitancy Factorsmentioning
confidence: 99%